Antazoline for pharmacological cardioversion of atrial fibrillation: the results of the high-volume multicenter CANT study. (25th November 2020) - Wybraniec, M; Maciag, A; Miskowiec, D; Ceynowa-Sielawko, B; Balsam, P; Wrobel, W; Farkowski, M; Cwiek-Rebowska, E; Szolkiewicz, M; Ozieranski, K; Krzowski, B; Kozinski, M; et al.
Abstract: Background: Antazoline mesylate represents a first generation antihistamine with quinidine-like antiarrhythmic properties, which allows for rapid and effective termination of atrial fibrillation (AF). Despite its widespread use in Polish emergency departments, paucity of data exists concerning safety and efficacy of antazoline in comparison to other antiarrhythmic agents. Purpose: This study aimed to evaluate the pooled hitherto data on effectiveness and safety of pharmacological Cardioversion with intravenous ANTazoline (CANT Study) in short-duration atrial fibrillation. Methods: This retrospective observational study was performed in 5 medical centers and comprised 1300 patients with paroxysmal or persistent AF who underwent emergent pharmacological cardioversion in the real-world setting of emergency or cardiology department. The choice of antiarrhythmic drug was left to the discretion of attending physician. The exclusion criteria involved permanent AF, other supraventricular arrhythmias, including atrial flutter, chronic antiarrhythmic therapy or preemptive electrical cardioversion. The primary endpoint was restoration of sinus rhythm up to 12 hours after antiarrhythmic drug infusion. The combined safety endpoint was bradycardia <45 bpm, hypotension, syncope or death. Results: The mean age of study population was 67.7±11.6 years and the majority of patients were men (52.9%). The median AF episode duration was 10 (4; 24) hours, while median CHA2DS2-VASc score was 3 (2; 4) pts. Antazoline alone was administered in 45.6% of patients (n=593); amiodarone in 22.1% (n=287); propafenone in 11.5% (n=150); sotalol in 0.5% (n=6), while 20.3% (n=264) received overlapping antiarrhythmic therapy. Antazoline had the highest rhythm conversion rate (Figure), which was comparable to propafenone (78.2% vs 72.7%; RR 1.08; 95% CI:0.97–1.20; P=0.175) and superior to amiodarone (vs 66.9%; RR 1.17, 95% CI:1.07–1.28; P=0.0008) and collective amiodarone/propafenone/sotalol treatment (vs 68.6%; RR 1.14; 95% CI:1.06–1.23; P=0.0006). The rate of combined safety endpoint was comparable in patients treated with antazoline and other antiarrhythmic drugs (5.2% vs 3.9%; P=0.297). Among patients treated with antazoline, 29 exhibited bradycardia <45 bpm and 5 patients suffered from hypotension, but no case of syncope, nor in-hospital death was reported. Conclusion: Antazoline appears to be an effective antiarrhythmic drug for cardioversion of atrial fibrillation, which is associated with low rate of relatively benign adverse events. Funding Acknowledgement: Type of funding source: None